From Middle Ages to Modern Time: Karelian female name system. - Kuzmin, Denis (Finnisch-Ugrische Forschungen, 2019)
This paper offers an analysis of the system of female names used among the Karelian population. In addition to the analysis of the forms of Christian names used in the past and present in the territory populated by ethnic Karelians in the Republic of Karelia, as well as in Finland and the Tver and Leningrad Regions, an attempt is made to reconstruct the pre-Christian female name system of Medieval Korela. An important observation is that, as opposed to pre-Christian male names, which can be uncovered not only in documents but also in Karelian surnames and toponymy, there are no documented traces of female pre-Christian names from the Karelian population. At present, the main source of knowledge about Finnic pagan female names is, admittedly, oral folk poetry. The author, however, believes that there is another important source of information in addition to folklore, i.e. cow names, which can potentially offer quite a bit of data about the pre-Christian female name system of the Medieval Karelians. The pre-Christian system of female names began to gradually vanish from the Karelian land as Orthodoxy took over. After the baptizing event in 1227, the introduction of the Russian Orthodox onomasticon into the Karelian milieu led to the emergence of multiple vernacular variants. To account for these, the author analyzes the main patterns in the phonetic adaptation of Russian-language forms of female names in the Karelian language.